Method validation for the determination of iodine in urine by ammonium persulfate digestion with spectrophotometric detection of the Sandell-Kothoff reaction - Serafico, Michael E.; Ulanday, Joselita Rosario C.; Perlas, Leah A. (2011)
Urinary iodine excretion (UIE) has been widely regarded as a biochemical marker for prevention and control of iodine deficiency disorders (IDD). To determine UIE levels, most methods require pretreatment of urine sample before its colorimetric detection based on the Sandell-Kolthoff rection. In this study, a greener and safer oxidizing agent for the removal of iodine interferents in urine was used and validated. Three levels of pooled urine sample and a sample taken from the interlaboratory comparison used as control were analyzed for UIE using the ammonium persulfate method. Spectrophotometric detection of iodine in urine at 420 nm was performed after the addition of arsenous acid and ceric ammonium sulfate in the digested sample. The calibration curve was linear ranging from 0 to 800 ug/L. The detective limit was 0 ug/L and the quantitation limit was 0.2ug/L urinary iodine. The method had an intra-assay coefficient of variation (CV) of 26.3% for the low, 4.1% for medium and 2.2% for the high UIE level controls. The inter-assay CV resulting from inter-analyst and inter-instrument analyses were 15.7% and 3.8% respectively. The validated method for urinary iodine determination is fast, safe, and economical.
Keywords: Urine; Iodine deficiency diseases